Perfil socioeconómico de los estudiantes de la carrera de Enfermería y su relación con el rendimiento académico, período 2018 - 2019 - Borja Borja, Margarita Felicidad (2019)
During the course of the nursing career it is essential to have an economic support that allows students to contribute resources for the acquisition of materials associated with the educational plan. The main objective of this research is to identify the socioeconomic profile of nursing students and their relationship with academic performance, which was developed in the Faculty of Health Sciences and the Human Being of the State University of Bolívar. In the theoretical framework, bibliographic references were taken from different authors who with their knowledge allowed us to deepen the problem in the studyand assimilate the criteria issued by them at the time, in addition to the knowledge provided byeach of the researchers. The research was conducted under a quantitative approach to descriptive ly the situation of nursing students at the State University of Bolívar. To this end, a survey was applied to define the socioeconomic profile, academic performance and the relationship between both variables. By applying the Pearson chi-square statistical test it was determined that there was a degree of relationship in both variables, however with an analysis of the linearity of the behavior through a Pearson correlation, it was determined that there is no marked linearity that allows to establish in a predictive way that the academic performance is affected by the economic conditions of the students. In this same order, it was concluded that the academic performance of the population is significant ly low and that the socioeconomic conditions are not the most favorable for the optimal development of the aspects that involve university student performance Keywords: socioeconomic profile, academic performance, students.